PENGARUH LIVE STREAMING, FEAR OF MISSING OUT (FOMO), DAN PAY LATER TERHADAP DISONANSI KOGNITIF PASCA PEMBELIAN MELALUI IMPULSE BUYING SEBAGAI VARIABEL MEDIASI PADA GENERASI Z PENGGUNA SHOPEE - Alfina Nisa Ameilia; Ristianawati Dwi Utami (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2026)
This study aims to examine the effects of live streaming, Fear of Missing Out (FoMO), and pay later on post-purchase cognitive dissonance through impulse buying as a mediating variable among Generation Z Shopee users. Grounded in the Stimulus-Organism-Response (S-O-R) Theory, this quantitative study explains how technological, financial, and psychological stimuli influence impulsive buying behavior and its psychological consequences. Primary data were collected through an online questionnaire distributed via Google Forms to 200 Generation Z respondents in the Special Region of Yogyakarta who actively used Shopee Live and SPayLater. Respondents were selected using purposive sampling, and the data were analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS) with SmartPLS 4. The findings reveal that live streaming, FoMO, and pay later have positive and significant effects on impulse buying. Furthermore, impulse buying significantly influences post-purchase cognitive dissonance and mediates the relationships between the three independent variables and post-purchase cognitive dissonance.